TEKNIK PENILAIAN PRAKTIK SHOLAT SUNAT DI SEKOLAH MENENGAH PERTAMA - Wihendar, Asep; Sriwahyudi, Doni; Kurniawati, Neng; Supardi, Edi (PAI RAFAH, 2024)
Evaluation techniques play crucial roles in any testing process implemented at any level of educational institution and in any kind of learning subject, including Islamic learning evaluation. They deliver beneficial and complete information both to teachers and to test administrators about how far instructional goals have been achieved. They also serve some feedback to analyze to ensure that the next testing occasion will be held more effectively, efficiently, and successfully. There have been a lot of kinds of evaluation techniques, one of which used in administering practical evaluation tools of Islamic learning conducted at SMP N 1 Sukaresmi has been called the checklist rubric technique. This study tries to find out the process of practical testing on sunnah prayer using the checklist rubric technique for the third-grade students of SMP N 1 Sukaresmi. The methods used were descriptive qualitative in which the data was gathered and collected through some observations, visitations, and inspections or supervisions as the qualified teknikts. The study brought about the fact that the practical evaluation using the checklist rubric has enabled and enhanced the test administrators to get clear and almost complete data of students’ achievements. Besides, using this kind of technique has made the evaluation easier, more simple, and more economical